S71 Influence of age on clinical phenotypes of incident idiopathic pulmonary arterial hypertension. Results from the pulmonary hypertension registry of the UK and Ireland. (2nd December 2011) - Ling, Y; Johnson, M K; Kiely, D; Condliffe, R; Elliot, C; Gibbs, S; Howard, L; Pepke-Zaba, J; Sheares, K; Corris, P; Fisher, A; Lordan, J; et al.
Abstract : Introduction and Objectives: The age of patients with idiopathic pulmonary arterial hypertension (IPAH) has increased since the NIH registry. It is postulated that older IPAH patients may have a different disease phenotype compared to their younger counterparts. Methods: Retrospective observational study of all consecutive incident cases of IPAH, heritable and anorexigen-associated pulmonary arterial hypertension diagnosed in all eight pulmonary hypertension centres in the UK and Ireland between 1st January 2001 and 31st December 2009. Patients were divided into younger and older subgroups by the median age (57 years). Results: Of 646 incident cases (mean age=54), 22% were over the age of 70 and 3% over age 80. Younger patients had higher % female (71% vs 56%), shorter duration of symptoms (median 15 months vs 21 months), better functional class (18% in functional class I/II vs 10%), exercise capacity (6-minute walk distance 325 m vs 217 m) and higher % predicted DLCO (65% vs 47%) compared to older patients. Older patients were more likely to present with peripheral oedema (41% vs 28%) whereas younger patients were more likely to complain of syncope (30% vs 10%), presyncope (14% vs 7%) and fatigue (15% vs 9%) at the time of diagnosis. Younger patients had higher mean pulmonary artery pressure (56 mm Hg vs 49 mm Hg) and pulmonary vascular resistance index (24 WU.m 2 vs 21 WU.m 2 ) but lower wedge pressure (9 mm Hg vs 10 mm Hg) compared to older patients. Patients in the highest age quartile had the worst survival [Abstract S71 figure 1 ]. Conclusion: Older incident IPAH patients appear to have a different disease phenotype compared to younger patients. IPAH is no longer a disease that affect predominantly young female only.